Wine Supply Chain Coordination in the Hospitality Industry: การประสานงานของโซ่อุปทานของไวน์ในอุตสาหกรรมการบริการ - Akkaranggoon, Supalak (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2017)
The purpose of this research is to examine supply chain coordination practice in the wine supply chain in relation to the hospitality industry, Thailand. The main objectives of this paper are (i) to describe the practice with regard to wine supply chain coordination within the hospitality industry and (ii) to compare the practice of wine supply chain coordination within the hospitality industry in Thailand and the theory. The study employs a qualitative approach to address the research problem. This paper is part of a wine supply chain research project investigating into wine supply chain practice in Thailand. The primary data were collected through one-on-one interviews with supply chain members of the wine supply chain. The results suggest coordination practice found in the hospitality industry reflects the traditional business practice. The characteristics of supply chain practice of the hospitality in Thailand are reported. The paper also identifies the discrepancy between the practice and theory of supply chain management. Discovered issues from the data are also discussed, and suggestions for future work are outlined.